Impact of cannabis abuse on the occurrence of stroke in young people: a systematic review and meta-analysis - Liu, Dongxue; Yang, Liu; Liu, Peiqi; Wang, Yujiao; Gao, Lan (Frontiers in Neurology, 2024)
The incidence of stroke in young people has risen significantly, it can easily lead to often leaving physical 2 disability, swallowing dysfunction, cognitive dysfunction and so on, etc., which has a heavy impact on the family and society.Risk factors of stroke incidence in young people are different from those of traditional stroke, and drug abuse is a high-risk factor. However, the extent of the impact of drug abuse on the occurrence of stroke in young people and the rate of disability are unclear. For further clarification and to provide evidence to support the primary prevention of stroke in young people, this systematic review and meta-analysis summarizes the latest information and results of previous studies.A systematic search of the PubMed, EMBASE, Cochrane Library, and Web of Science databases to April 2023 was performed. This included observational studies comparing stroke risk estimates in drug abusers and non-users.Results: This review comprised six seven observational studies regarding cocaine and cannabis use, with 119284152119,286,396 participants. Found a substantial link between cannabis substance abuse and the risk of stroke(OR = 1.14,95% CI [1.08,1.20]), however, there was a large heterogeneity between the evidence (I² = 89%, p < 0.001). After adjusting for confounders (smoking OR alcohol abuse), we found a stronger association between cannabis abuse and stroke in young adults (OR=1.21,95% CI [1.12,1.29]).. Subgroup analyses showed that cannabis abuse had no significant difference between ischemic and hemorrhagic stroke, meta-analysis of the random-effects model showed that significant heterogeneity was due to the type of stroke, and the difference was statistically significant (p = 0.43).The result of our systematic review and meta-analysis showed that cannabis abuse has a more significant effect on the occurrence of stroke in young people , but it was not possible to distinguish whether cannabis abuse was more likely to cause ischemic or hemorrhagic stroke. In addition, there is a need for further research to clarify the impact of different drug types, dosages, and behaviors on stroke.